2012
DOI: 10.1186/1477-7819-10-231
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lobular carcinoma of the breast masquerading as a primary rectal cancer

Abstract: BackgroundColorectal metastasis of lobular carcinoma of the breast is a diagnostic challenge. It may macroscopically simulate primary colon cancer or inflammatory bowel disease. In some cases, the interval between the primary breast cancer and metastatic colorectal lesions is so long that the critical records for diagnosis including history might be lost or missed.Case presentationReported herein is a case of metastatic lobular carcinoma of the breast masquerading as a primary rectal cancer developed in a 62-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
(24 reference statements)
3
31
0
Order By: Relevance
“…The invasive lobular cancer that represents 5%-10% of primary breast cancers, frequently involves unusual metastatic sites such as the gastrointestinal tract, the gynaecological organs, the peritoneum and meninges (10)(11)(12)(13)(14) in contrast to the invasive ductal cancer that follows the more conventional metastatic pattern of breast cancers and metastasizes in liver, lungs and brain (15,16).…”
Section: Epidemiologymentioning
confidence: 99%
“…The invasive lobular cancer that represents 5%-10% of primary breast cancers, frequently involves unusual metastatic sites such as the gastrointestinal tract, the gynaecological organs, the peritoneum and meninges (10)(11)(12)(13)(14) in contrast to the invasive ductal cancer that follows the more conventional metastatic pattern of breast cancers and metastasizes in liver, lungs and brain (15,16).…”
Section: Epidemiologymentioning
confidence: 99%
“…One French retrospective cohort showed the median time interval from diagnosis to gastric metastases was 57 months . In two Japanese retrospective cohorts, the median time interval was beyond 3 years and 6 years. In one Japanese case report, the time interval was up to 11 years…”
Section: Discussionmentioning
confidence: 99%
“…First, almost all the metastatic colonic lesions present like primary GI tumors on radiography and endoscopy. They can present as poorly differentiated, lintis plastica type GI lesion and can be misdiagnosed as primary GI carcinoma [8]. Calafat et al and Easter et al reported metastasis of lobular breast carcinoma that presented as Crohn's disease [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The median interval between breast cancer and GI metastases is 6 or 7 years [8]. In many patients the history of primary breast cancer is known but Harsløf et al reported a case of colon metastasis compatible with lobular carcinoma of the breast although the primary breast cancer was never identified [13].…”
Section: Discussionmentioning
confidence: 99%